Facilitators and barriers of appropriate and timely initiation of intravenous fluids in patients with sepsis in emergency departments: a consensus development Delphi study - Gladis Kabil; Steven A. Frost; Deborah Hatcher; Amith Shetty; Stephen McNally (BMC, 2023)
Abstract Background Sepsis is a life-threatening medical emergency in which appropriate and timely administration of intravenous fluids to patients with features of hypotension is critical to prevent multi-organ failure and subsequent death. However, compliance with recommended fluid administration is reported to be poor. There is a lack of consensus among emergency clinicians on some of the determinant factors influencing fluid administration in sepsis. Thus, the aim of this study was to identify the level of consensus among key stakeholders in emergency departments regarding the facilitators, barriers, and strategies to improve fluid administration. Methods The modified Delphi questionnaire with 23 statements exploring barriers, facilitators, and strategies to improve fluid administration was developed from the integration of findings from previous phases of the study involving emergency department clinicians. A two-round modified Delphi survey was conducted among key stakeholders with managerial, educational, supervision and leadership responsibilities using a "Reactive Delphi technique" from March 2023 to June 2023. The statements were rated for importance on a 9-point Likert scale. The RAND/UCLA Appropriateness Method (RAM) was used to identify the level of consensus (agreement/disagreement). Results Of the 21 panellists who completed Round 1 survey, 18 (86%) also completed Round 2. The panellists rated 9 out of 10 (90%) barriers, 3 out of 4 (75%) facilitators and all 9 (100%) improvement strategies as important. Out of the total 23 statements, 18 (78%) had agreement among the panellists. Incomplete vital signs at triage (Median = 9, IQR 7.25 to 9.00) as a barrier, awareness of importance of fluid administration in sepsis (Median = 9, IQR 8.00 to 9.00) as facilitator and provision of nurse-initiated intravenous fluids (Median = 9, IQR 8.00 to 9.00) as an improvement strategy were the highest rated statements. Conclusion This is the first Delphi study identifying consensus on facilitators, barriers, and strategies to specifically improve intravenous fluid administration in sepsis in Australia. We identified 18 consensus-based factors associated with appropriate and timely administration of intravenous fluids in sepsis. This study offers empirical evidence to support the implementation of the identified strategies to improve patient outcomes.